PROSES MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KECAMATAN MAGETAN KABUPATEN MAGETAN PROVINSI JAWA TIMUR - Heru Sulistiyo (ipdn, 2019)
Development Planning Deliberation Process in Magetan Subdistrict, Magetan Regency, East Java Province. Planning is the process of organizing and determining appropriate actions through deliberation. This process begins with an inventory of needs taking into account the available strength. In development planning meetings, participants must optimize, because the community is the main picker of the results of development. The purpose of this study is to describe the real conditions of the stages of development planning meetings at the sub-district level so that the community generally understands the series of sub-district level development planning deliberation processes, and can participate in achieving better results. The government must absorb input from the bottom in addition to providing information about the priority level and strength of the indicative ceiling, to create integration, synchronization and synergy between the region and the center. The method used in this study is descriptive method, which describes the real conditions based on the processes and facts that exist. The result is that Magetan Subdistrict has carried out development planning deliberations smoothly, in accordance with the technical guidelines set by the District Government. Sub-district level development planning meetings are participatory development planning forums, from top to bottom, and from the bottom up. Keywords: planning, society participation, integration, synergy